Perception of teachers and agriculture vocational high school students on stem-based biology learning - R F Mustari; A Widodo; W Purwianingsih (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
STEM-based learning is now a trend in education. This study describes teacher andstudent perceptions of STEM. The researcher involves biology teachers and 72 students whoare caught from six classes in grade X at Cianjur Agriculture Vocational High School, WestJava, Indonesia. The method used in this research is descriptive. Data were obtained based onquestionnaire answers regarding opinion, attitude, and environmental roles on respondentsregarding STEM-based learning. The result showed that 57.60% of students were interested inSTEM-based learning, and 66.52% of students had readiness to participate in STEM-basedlearning. As much as 67.54% of students recognize that careers in the STEM field are goodand promising, supported by 70, 92% of students recognize that STEM-based learning isbeneficial to their lives. The results of teacher answers on the questionnaire that as many as70.92% said that STEM useful for his life in the future. Master agrees that 100% career inSTEM field is good. Teachers think that their students are interested in STEM as much as71.42%. These two perceptions between teacher and student are in agreement.